Primary Tuberculous Mastitis: The first report from Syria. (2020) - Kayali, Sadallah; Alhamid, Aos; Kayali, Ayman; Danial, Aghyad Kudra; Brimo Alsaman, Muhamad Zakaria; Alhamid, Ahmad; Ayoub, Kusay
Highlights: Breast TB is not commonly seen in medical practice. Surgical biopsy is necessary to confirm the diagnosis of tuberculous mastitis. Usually Anti-tuberculous therapy is the main treatment for breast TB. Minimal surgery is performed to remove any residual lesions. Abstract: Introduction: Primary breast tuberculosis is a rare form of extrapulmonary tuberculosis even in endemic regions. To our knowledge, this is the first report of Primary breast tuberculosis from Syria. Case presentation: We report a case of a 37-year-old female who admitted to the surgical clinic with a 4-month history of gradually growing mass in the breast. On physical examination there were a palpable mass, painful superficial abscess in her left lateral upper quarter of breast, redness and nipple retraction and ulceration. The patient history and physical examination were clear except for uncontrolled hypothyroidism. Radiological tests including mammography, echography and laboratory investigations were performed. The patient underwent lumpectomy. Histopathologic examination showed caseating Tuberculous Mastitis and a large tuberculous abscess, with no malignancy. Patient was put on anti-tubercular chemotherapy, but recurred after three months with three masses in the same area because she did not adhere to the treatment. Lumpectomy and Anti-tuberculous therapy were repeated again with close follow-up, and the patient recovered. Discussion: Primary breast tuberculosis forms about 0.025-0.1 % of all surgically treated breast diseases. Diagnosis is based on bacteriological and histological examination. We can get higher accuracy in diagnosis by biopsy such as a core needle or surgical biopsy, surgical biopsy is necessary to confirm the diagnosis of tuberculous mastitis. Conclusion: Tuberculous mastitis is extremely rare variant of extrapulmonary tuberculosis. However, it should be kept in the mind of physicians and pathologists while approaching a breast mass, especially in endemic area.